Ferrocenyl–Bipyridinium Cations and Their Platinum Complexes Related to Viologens – Preparation, Redox Properties, and Crystal Structures. Issue 13 (26th March 2015) - Mochida, Tomoyuki; Funasako, Yusuke; Nezu, Yukiko; Hagiwara, Koji; Horikoshi, Ryo
Abstract: N ‐R 1 ‐ N′ ‐R 2 ‐4, 4′‐Bipyridinium and N ‐R 1 ‐4, 4′‐bipyridinium salts containing ferrocenyl substituents were prepared as donor–acceptor compounds (R 1 = ferrocenyl, ferrocenylphenyl; R 2 = ferrocenyl, ferrocenylphenyl, phenyl, methyl). Platinum(II)‐bridged diferrocene compounds were prepared by using the N ‐R 1 ‐4, 4′‐bipyridinium ligands. These compounds display multistage redox properties. The redox potentials of the ferrocenyl and bipyridinium moieties in these compounds are independently affected by molecular modifications, which indicates that conjugation between the donor and acceptor moieties is less effective. Single‐crystal X‐ray diffraction analyses revealed large twist angles between the two moieties in the solid state. The compounds exhibit broad charge‐transfer absorption bands in the range 450–800 nm. No electronic communication was observed between the terminal ferrocenes in the diferrocene complexes. Abstract : 4, 4′‐Bipyridinium cations bearing ferrocenyl or ferrocenylphenyl substituents at the N ‐positions were prepared as donor–acceptor compounds. Platinum(II)‐bridged diferrocene compounds were also prepared by using bipyridinium cations. These cations display multistage redox properties, and the compounds exhibit broad charge‐transfer absorption bands in the range 450–800 nm.